Depression of lncRNA MINCR antagonizes LPS-evoked acute injury and inflammatory response via miR-146b-5p and the TRAF6-NFkB signaling - Wei Gao; Ying Zhang (BMC, 2021)
Abstract Background Inflammation plays an important role in the development of acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). The long non-coding RNA (lncRNA) MINCR is closely related to inflammation injury. This study was performed to explore the protective effects and mechanisms of MINCR in lipopolysaccharide (LPS)-induced lung injury and inflammation. Methods The expression levels of MINCR and miR-146b-5p in lung tissue status were detected by using quantitative real-time polymerase chain reaction (qRT-PCR), hematoxylin and eosin staining, immunohistochemical staining, and terminal deoxynucleotidyl transferase dUTP nick end labeling assay. Enzyme-linked immunosorbent assay and Western blotting analysis were used to detect the expression of inflammatory factors such as tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-10 in lung tissue. The relationship between MINCR, miR-146b-5p, and TRAF6 was explored using bioinformatics analysis and luciferase assay. Results The expression levels of MINCR were increased in a mouse model of LPS-induced ALI and small airway epithelial cells (SAECs). shMINCR resulted in increased cell viability and decreased apoptosis, which protected against LPS-induced cell damage. shMINCR can inhibit the formation of neutrophil extracellular traps, neutrophil numbers, myeloperoxidase activity, and the production of inflammatory cytokines IL-6, IL-1β, and TNF-α induced by LPS. The silencing of miR-146b-5p reversed the effects of MINCR on LPS-induced lung damage. Sh-MINCR decreased the expression levels of TRAF6 and p-P65 in LPS-induced SAECs and lung tissues. Co-transfection of sh-MINCR with miR-146b-5p inhibitor reversed the effect of sh-MINCR on the expression of TRAF6 and p-P65. Conclusions MINCR may induce alveolar epithelial cell injury and inflammation and aggravate the progression of ALI/ARDS through miR-146b-5p and TRAF6/NF-κB pathways, which would provide a promising target for the treatment of ALI/ARDS.